2021
DOI: 10.1136/bmjoq-2021-001482
|View full text |Cite
|
Sign up to set email alerts
|

Reducing potentially avoidable tasks in a hyperacute stroke unit

Abstract: The workflow in a stroke unit can be very high, and this is especially noticeable during evening and night shifts, where staffing is reduced but the patient’s need for frequent and intensive care is not. The specialised and standardised settings in a stroke regime are constant and demanding for healthcare providers who, therefore, must work efficiently. Patient admissions, acute situations and routine tasks are major contributors to the burden of work during evening and night shifts for junior doctors on call.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…In a tertiary care hospital in Japan, the development and implementation of a stroke code protocol and educational workshops resulted in decreased time from stroke recognition to neurologist assessment (91-35 minutes; P=0.002) and to neuroimaging (123-74 minutes; P=0.013), but no changes in thrombolysis or endovascular therapy were observed. 13 Acute Hospital Care QI Several studies described in-hospital care QI initiatives including in Nova Scotia (Canada), 14 Australia, 15 and in single institutions in Denmark, 16 and East Kent (United Kingdom). 17 The studies varied in terms of the QI intervention; some were multifaceted, 14 whereas others focused on a single QI strategy (eg, PDSA cycles, 16,17 external facilitation 15 ).…”
Section: Ctmentioning
confidence: 99%
See 2 more Smart Citations
“…In a tertiary care hospital in Japan, the development and implementation of a stroke code protocol and educational workshops resulted in decreased time from stroke recognition to neurologist assessment (91-35 minutes; P=0.002) and to neuroimaging (123-74 minutes; P=0.013), but no changes in thrombolysis or endovascular therapy were observed. 13 Acute Hospital Care QI Several studies described in-hospital care QI initiatives including in Nova Scotia (Canada), 14 Australia, 15 and in single institutions in Denmark, 16 and East Kent (United Kingdom). 17 The studies varied in terms of the QI intervention; some were multifaceted, 14 whereas others focused on a single QI strategy (eg, PDSA cycles, 16,17 external facilitation 15 ).…”
Section: Ctmentioning
confidence: 99%
“…13 Acute Hospital Care QI Several studies described in-hospital care QI initiatives including in Nova Scotia (Canada), 14 Australia, 15 and in single institutions in Denmark, 16 and East Kent (United Kingdom). 17 The studies varied in terms of the QI intervention; some were multifaceted, 14 whereas others focused on a single QI strategy (eg, PDSA cycles, 16,17 external facilitation 15 ).…”
Section: Ctmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 7 A QI project demonstrated that it is possible to improve clinical practices and reduce potential avoidable tasks in a busy emergency environment of healthcare professionals by implementing low-cost changes such as education, knowledge sharing, checklists and feedback. 8 Systematic verbal transfer of information is essential to improve efficiency and both patient safety and experience. 9 One QI demonstrated improvement of the written documentation by introducing a ‘handover sticker’.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial number of QI projects exists on interventions that aim to improve patient flow in the emergency setting 6 7. A QI project demonstrated that it is possible to improve clinical practices and reduce potential avoidable tasks in a busy emergency environment of healthcare professionals by implementing low-cost changes such as education, knowledge sharing, checklists and feedback 8. Systematic verbal transfer of information is essential to improve efficiency and both patient safety and experience 9.…”
Section: Introductionmentioning
confidence: 99%